Constitutionalism and the enlargement of Europe - Sadurski, Wojciech, 1950- (Oxford : Oxford University Press, 2012)
Written at the intersection of law and political science, this book adopts an original perspective on the legal implications of the eastward enlargement of the Council of Europe and the European Union. Case studies offer a novel examination of the development of legal norms and institutions within these supranational bodies.
Description based on online resource; title from PDF title page (viewed on Aug. 13, 2012).
Includes bibliographical references and index.
Keywords: European Union; Council of Europe; European Court of Human Rights; Constitutional law -- Europe; Europe -- Economic integration -- Political aspects